Effect of denture cleansers on color stability and surface roughness of denture bases fabricated from three different techniques: Conventional heat‐polymerizing, CAD/CAM additive, and CAD/CAM subtractive manufacturing - Mehrab Takhtdar; Nahid Azizimoghadam; Mohammad Hasan Kalantari; Mina Mohaghegh (Wiley, 2023)
Abstract Purpose Denture base materials are commonly exposed to different denture cleansers which can affect their essential properties. This study aimed to assess the effect of denture cleansers on color stability and surface roughness of poly methyl methacrylate (PMMA) denture bases fabricated from different techniques: Conventional heat‐polymerizing, CAD/CAM additive and CAD/CAM subtractive. Materials and Methods In this in vitro study, 24 disc‐shaped specimens were fabricated by the mentioned methods for each group. The initial color and surface roughness of specimens were recorded. The specimens were randomly divided into three subgroups (n = 8): a control subgroup (distilled water), and two experimental subgroups of bioactive oxygen tablet (Corega) and 1% sodium hypochlorite solution. Then they were immersed in the solutions simulating 180 days of clinical use. Color change (∆E) was measured by a spectrophotometer according to the CIE L*a*b* color space and the American National Bureau of Standards (NBS = 0.92 × ∆E). Final surface roughness was recorded by a profilometer and its change was calculated. The Kruskal-Wallis test followed by the Wilcoxon signed rank test were used for statistical analyses (α = .05). Results The conventional and CAD/CAM subtractive groups showed an increase in surface roughness following immersion in hypochlorite solution (p < .05). After immersion in the solutions, the highest surface roughness was noted in the conventional group, and the lowest in the CAD/CAM additive group. The CAD/CAM additive group experienced a significant color change in hypochlorite solution (p < .05) and showed the highest color change while the CAD/CAM subtractive group showed the lowest color change in all denture cleanser solutions. Conclusion Although the CAD/CAM additive denture base resins had the lowest surface roughness after exposure to denture cleanser solutions, they showed significant color change, which should be taken into account. Using hypochlorite as a denture cleanser should be cautioned due to its negative effects on the surface roughness and color stability of denture base materials.